Simplified 89Zr-Labeling Protocol of Oxine (8-Hydroxyquinoline) Enabling Prolonged Tracking of Liposome-Based Nanomedicines and Cells - Andras Polyak; Jens P. Bankstahl; Karen F. W. Besecke; Constantin Hozsa; Wiebke Triebert; Rajeswara Rao Pannem; Felix Manstein; Thomas Borcholte; Marcus Furch; Robert Zweigerdt; Robert K. Gieseler; Frank M. Bengel; et al. (MDPI AG, 2021)
In this work, a method for the preparation of the highly lipophilic labeling synthon [89Zr]Zr(oxinate)4 was optimized for the radiolabeling of liposomes and human induced pluripotent stem cells (hiPSCs). The aim was to establish a robust and reliable labeling protocol for enabling up to one week positron emission tomography (PET) tracing of lipid-based nanomedicines and transplanted or injected cells, respectively. [89Zr]Zr(oxinate)4 was prepared from oxine (8-hydroxyquinoline) and [89Zr]Zr(OH)2(C2O4). Earlier introduced liquid-liquid extraction methods were simplified by the optimization of buffering, pH, temperature and reaction times. For quality control, thin-layer chromatography (TLC), size-exclusion chromatography (SEC) and centrifugation were employed. Subsequently, the 89Zr-complex was incorporated into liposome formulations. PET/CT imaging of 89Zr-labeled liposomes was performed in healthy mice. Cell labeling was accomplished in PBS using suspensions of 3 × 106 hiPSCs, each. [89Zr]Zr(oxinate)4 was synthesized in very high radiochemical yields of 98.7% (96.8% ± 2.8%). Similarly, high internalization rates (≥90%) of [89Zr]Zr(oxinate)4 into liposomes were obtained over an 18 h incubation period. MicroPET and biodistribution studies confirmed the labeled nanocarriers' in vivo stability. Human iPSCs incorporated the labeling agent within 30 min with ~50% efficiency. Prolonged PET imaging is an ideal tool in the development of lipid-based nanocarriers for drug delivery and cell therapies. To this end, a reliable and reproducible 89Zr radiolabeling method was developed and tested successfully in a model liposome system and in hiPSCs alike.